CHANGES IN PHYSICO-CHEMICAL PROPERTIES OF ASSAM LEMON (CITRUS LIMON BURM.) AT DIFFERENT STAGES OF FRUIT GROWTH AND DEVELOPMENT - C. MUKHIM; A. NATH; BIDYUT C. DEKA; T. L. SWER (The Bioscan, 2015)
An experiment was undertaken under mid hills of Meghalaya, India, in order to study the changes in physico- chemical properties of Assam lemon at different stages of fruit growth and development. The present study significantly showed that fruits harvested at 120 to 130 days after fruit set developed acceptable physico-chemical qualities with optimum fruit weight (109.28 to 112.95 g), fruit size (Length= ≥ 81.05mm, Breadth= ≥50.13mm), specific gravity (0.97 to 1.01), juice content (37.68 to 41.23 %), TSS (≥6.3 °Brix), titratable acidity (4.18 to 4.35%), ascorbic acid (≥32.41 mg/100g), TSS: acidity (≥1.51) and these may be considered as the most reliable maturity indices for taking harvest decision in Assam lemon fruit.